Association between abnormal glycoprotein and diabetic peripheral neuropathy in patients with type 2 diabetes mellitus - Zhu, Dongmei; Kong, Deyue; Li, Qian; Jiang, Hemin; Shen, Ziyang (Frontiers in Endocrinology, 2025)
Background and objectivesTo investigate the association between serum abnormal glycoprotein (AP) and diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (T2DM).Materials and methodsThis cross-sectional study enrolled 476 patients with T2DM. DPN was diagnosed using the Toronto Clinical Neuropathy Score (TCNS) and nerve conduction studies. The association between AP and DPN was evaluated using multivariable logistic regression, restricted cubic spline analysis (RCS), and receiver operating characteristic (ROC) curve analysis.ResultsSerum AP levels were significantly higher in patients with DPN than in those without (P < 0.001). After adjusting for multiple confounders, elevated AP emerged as an independent risk indicator for DPN (OR = 1.024, 95% CI: 1.012-1.036). A non-linear relationship was observed, with a marked increase in DPN risk when AP levels exceeded an inflection point of 119.628 μm². Combining AP with clinical variables significantly enhanced predictive accuracy for DPN, increasing the area under the curve (AUC) from 0.686 to 0.805.ConclusionsElevated serum AP represents a novel and independent risk indicator for DPN in patients with T2DM. Its integration into clinical practice may facilitate early detection for DPN.